Supporting beginning rural teachers : Lessons from successful schools - White, Simone; Lock, Graeme; Hastings, Wendy; Reid, Joanne; Green, Bill; Cooper, Maxine (Albury, New South Wales : Australian Teacher Education Association (ATEA, 2009)
Across Australia and internationally, the vexed problem of staffing rural school remains a major issue affecting the educational outcomes of many rural students and their families. TERRAnova, (New Ground’ in Teacher Education for Rural and Regional Australia), is the name of a large Australian Research Council funded (2008-2010) project involving: a national study of pre-service preparation and rural incentive schemes offered by both University and State government agencies, a longitudinal study of beginning teachers who take up rural appointments and a study of communities where teacher retention is high. In 2008 calls for nominations for rural schools with high rates of retaining beginning teachers were sought (over three years), and twenty-four of nearly fifty nominated schools were selected as case studies. Each case study has involved researchers from the TERRAnova team travelling and staying as close to the community nominated as possible. Numerous teaching staff, parents and community members were invited to be interviewed and their recordings were transcribed. Five of these case studies have now been completed, and this paper examines common themes derived from the strategies that support beginning teachers in these rural communities. Key factors emerging to date from the data relate to particular models of rural school leadership, ongoing teacher learning and mentoring, and school support and innovative community practices.